Characterization of Thaumatin-like Gene Family Reveals Group V CaTLPs Drive Anthracnose Resistance in Pepper (Capsicum annuum) - Hao Wu; Jian Zeng; Cui Mao; Weifeng Huang; Chuanhong Li; Liya Yang; Xiaohan Zhang; Jiaxian Lin; Jianjun Lei; Yong Zhou; Zhangsheng Zhu; Jie Zheng (Horticulturae, 2025)
Pepper anthracnose is a globally devastating fungal disease caused by Colletotrichum spp. In this study, we explored the molecular mechanisms underlying anthracnose resistance in Capsicum annuum by comparing a resistant variety 225 with a susceptible variety 307. Phenotypic analysis revealed that variety 225 displayed stronger resistance than variety 307. Through comparative transcriptome analysis and weighted gene co-expression network analysis (WGCNA), 17 gene modules were identified, among which the salmon module showed a strong association with resistance in variety 225. Within this module, 18 hub genes—including Ca59V2g00372.1 (CaTLP6), encoding a thaumatin-like protein (TLP)—were significantly upregulated upon infection. A genome-wide analysis identified 31 CaTLP genes in C. annuum, with members of group V (such as CaTLP6) exhibiting induced expression post-inoculation of Colletotrichum scovillei. Subcellular localization analysis indicated that group V CaTLP proteins were associated with the plasma membrane, suggesting a role in pathogen recognition. These findings highlight the significance of CaTLP genes, particularly those in group V, in pepper’s defense against anthracnose caused by C. scovillei and offer promising targets for breeding resistant cultivars.